MEMBANGUN KELUARGA BAHAGIA (SMART) - Nasution, Khoiruddin (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2008)
Family formed through marriage between men and women is a blend of the two people who agreed to achieve happiness. Therefore, achieving the purpose of marriage is in principle the same as achieving happiness family members. Family members initially were husband and wife. Once they have a child thoroughbred. Then the family members grow with the child. The question then is how to build a family that can achieve happiness for its members, which is the title of this article is called the family happy (smart). This short article tries to answer these questions . To simplify the discussion, this paper is divided into four sub-topics, which began with the introduction. The second part is described the notion of marriage and the third part is written the purpose of marriage—explanation understanding of marriage to shape perceptions and concepts are in line with the purpose of marriage. Then in the fourth section is discussed the principles of how to build a happy family as the purpose of marriage.[Keluarga yang terbentuk lewat perkawinan antara dua orang laki-laki dan perempuan, merupakan perpaduan dari dua orang tersebut yang setuju untuk meraih kebahagiaan. Karena itu, mencapai tujuan perkawinan pada prinsipnya sama dengan mencapai kebahagiaan anggota keluarga. Anggota keluarga pada awalnya adalah suami dan isteri. Setelah berketurunan mereka mempunyai anak. Maka anggota keluarga bertambah dengan anak. Pertanyaannya kemudian adalah, bagaimana membangun keluarga yang dapat mencapai kebahagiaan bagi anggotanya, yang dalam judul tulisan ini disebut keluarga bahagia (smart). Tulisan singkat ini berusaha menjawab pertanyaan tersebut. Untuk mempermudah pembahasan, tulisan ini dibagi menjadi empat sub bahasan, yang dimulai dengan pendahuluan di bagian awal. Bagian kedua diuraikan pengertian perkawinan dan bagian ketiga dituliskan tujuan perkawinan. Penjelasan pengertian perkawinan untuk membentuk persepsi dan konsep yang sejalan dengan tujuan perkawinan. Kemudian pada bagian keempat dibahas prinsip-prinsip bagaimana membangun keluarga bahagia sebagai tujuan perkawinan.]